Implementation and efficacy of a teacher intervention in dialogic mathematics classroom discourse in Hong Kong primary schools. (2021) - Ni, Yujing; Shi, Lian; Cheung, Alan; Chen, Gaowei; Ng, Oi-Lam; Cai, Jinfa
Highlights: The intervention aimed at developing teachers' conceptual and practical tools to engage students. The intervention teachers reduced the discourse behavior to evaluate a student's response. Their discourse behaviors increased to prompt students to engage with others' ideas. Students responded to the changes by showing increased amount of classroom contribution. Abstract: The present study investigated the efficacy of an intervention program to assist teachers in the development of conceptual and practical tools for engaging students in dialogic classroom discourse. Sixteen fourth-grade mathematics teachers received 28 h of the intervention over a semester of 4 ½ months. Compared to the nonintervention group, the intervention teachers showed a reduced tendency to evaluate student responses and were more likely to promote students to engage with others' ideas. Students of the intervention group responded to the teachers' changes by demonstrating increased amount of contributions in classroom discussion. The results indicate that increasing awareness on dialogic classroom discourse provides an encouraging platform for teacher professional development to improve the quality of disciplinary teaching and learning.